Edukasi Proper Body Mechanics Untuk Mengurangi Nyeri Pinggang - Rosdiana, Ika; Wirastuti, Ken (Indonesian Journal of Community Services, 2024)
Back pain is a medical condition that has the potential to cause disability. The 2020 Global Burden of Disease, Injury and Risk Factors study, the number of people affected by low back pain reached 619 million globally, with a projection of reaching 843 million cases in 2050. The YLD Years Lived with Disability rate based on global age standards in 2020 reached 832 per 100,000, thus there has been an increase in the number of low back pain sufferers in each time period. Improper use of body mechanics when carrying out various activities can cause mechanical lower back pain. Proper Body Mechanics is a preventive way to maintain alignment, balance and back posture when carrying out activities. The Roland-Morris Disability Questionnaire (RMDQ) is one of the most widely used instruments to measure self-reported disability in patients with low back pain. RMDQ is an instrument to assess what percentage of clinical improvement over time is assessed based on serial analysis of scores. The aim of this PKW is to provide education about the importance of proper body mechanics for patients with low back pain in reducing pain and reducing recurrence. The method for implementing this PKW is to provide education about the importance of proper body mechanics to participants who experience back pain. Participants carry out proper body mechanics for 3 months. Before and after carrying out proper body mechanics, interviews were conducted using RMDQ. The results of this education showed that data from 22 participants showed that there had been an increase in function of 85.44% and a decrease in the level of disability from the RMDQ score. This provides evidence of the effectiveness of proper body mechanics in reducing low back pain